« Privé versus Public » - Oumaya Hidri Neys; Yamina Remichi (La Nouvelle Revue du Travail)
Notwithstanding French anti-discrimination law, some people’s physical appearance still hinders their labour market access. The present study explores in situ the importance of physical appearance during the receptionist recruitment process and tries to compare the public and private sectors in this respect. It findings are at odds with received wisdom.